Na jakie pytania mógłby odpowiedzieć tworzony w 2. dekadzie XXI w. model leksykalno- -derywacyjny polszczyzny XX w.? - Wierzchoń, Piotr (Investigationes Linguisticae, 2011)
This paper discusses a project to develop a lexico-derivational model of 20th-century Polish vocabulary. On the one hand, this model should be constructed in accordance with the Polish tradition of great lexico-derivational models such as Satkiewicz 1969, Smółkowa 1976, Jadacka 2001 and Waszakowa 2005. On the other hand, it should take into consideration new empirical material gained from the application of linguochronoligization theory (TLCH). A crucial part in the construction of the new model is played by lexical material from the first half of the 20th century, which by the end of the first decade of the 21st century was available only in very limited quantity, most of it coming from systematic, long-term extraction research carried out by Jan Wawrzyńczyk. Therefore this article describes the milestones which have led to the present state, in which it is possible to formulate a plan for the development of such a model. Moreover, the limitations and shortcomings of previous lexico-derivational models are discussed. As a result, a list of 37 questions which could be answered by the emerging model of Polish vocabulary is given. Also, selected graphs are presented to illustrate the diachronic dynamics of Polish vocabulary in the first half of the 20th century.